1986
DOI: 10.1007/bf00845119
|View full text |Cite
|
Sign up to set email alerts
|

Physical health correlates of Type A behavior in children and adolescents

Abstract: A physical examination including resting blood pressure, heart rate, Tanner scales, height, and weight was administered to 184 students in the fifth, seventh, and ninth grades. They completed the Physical Symptoms of Stress Inventory, Health Habits Inventory, and two self-monitoring logs of physical symptoms. School absenteeism, medical records, physician ratings, and family health history data were collected. No significant differences between high- and low-Type A behavior pattern (TABP) subjects were found o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0
1

Year Published

1988
1988
2001
2001

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(6 citation statements)
references
References 33 publications
2
3
0
1
Order By: Relevance
“…Similar findings have been noted in other Type A children (Eagleston et al, 1986) and in adult cardiac patients (Oldridge etal., 1978;Rejeskietal., 1984). However, although the convergence of these data are intriguing, one recent study failed to find Type A underutilization of child-initiated medical care (Matthews, Stoney, Rakaczky, & Jamison, 1986).…”
Section: Discussionsupporting
confidence: 91%
“…Similar findings have been noted in other Type A children (Eagleston et al, 1986) and in adult cardiac patients (Oldridge etal., 1978;Rejeskietal., 1984). However, although the convergence of these data are intriguing, one recent study failed to find Type A underutilization of child-initiated medical care (Matthews, Stoney, Rakaczky, & Jamison, 1986).…”
Section: Discussionsupporting
confidence: 91%
“…FOr years researchers have been encouraged to measure and statistically control neuroticism in their studies to address this issue (Costa & McCrae, 1987;Holroyd & Coyne, 1987), but few have heeded the call; personal goal researchers have yet to control for neuroticism in their work on the personality-illness relationship (see Emmons & King, 1988, Study 1, for the closest analog). In all three studies of the present research, neuroticism was measured and statistically controlled in testing the relationship between avoidance personal goals and symptom reports, Furthermore, several other personality variables that have also been empirically or theoretically linked to symptom reports (Type A personality, optimism, hope, behavioral inhibition system [BIS ] sensitivity, extraversion, and Nenroticism x Extraversion; see Eagleston et al, 1986;Fowles, 1988;Scheier & Carver, 1987;Snyder et al, 1991;Zautra, Finch, Reich, & Guarnaccia, 1991) were also included to more rigorously test the discriminant validity of the avoidance goals construct.…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…In all three studies of the present research, neuroticism was measured and statistically controlled in testing the relationship between avoidance personal goals and symptom reports. Furthermore, several other personality variables that have also been empirically or theoretically linked to symptom reports (Type A personality, optimism, hope, behavioral inhibition system [BIS] sensitivity, extraversion, and Neuroticism × Extraversion; see Eagleston et al, 1986; Fowles, 1988; Scheier & Carver, 1987; Snyder et al, 1991; Zautra, Finch, Reich, & Guarnaccia, 1991) were also included to more rigorously test the discriminant validity of the avoidance goals construct.…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…In a study using children, Matthews and Volkin (1981) showed that Type A subjectsrepon less physical fatigue than non-Type As as measured by a behaviorally-anchored seven point fatigue scale, suggesting the possibility that Type A children also use cognitive coping strategies and/or are better able to focus their attention and ignore distractions than non-Type A children. Eagleston et al (1986) found that Type A children may keep pushing themselves to perform even when physically ill, perhaps denying the meaning or severity of their symptoms. It may be that Type A children and adolescents simply have more experience at dealing with life stressors than others, and therefore have developed more effective and/or elaborate coping strategies.…”
Section: Attempts To Explain the Lower Self-concept Of Typementioning
confidence: 96%